Case Study: Transition to a Vegan Diet in an Elite Male Gaelic Football Player - Daniel Davey; Shane Malone; Brendan Egan (MDPI AG, 2021)
Vegan diets are increasingly of interest to athletes, but require a well-planned approach in order to mitigate the risk of potential adverse effects on nutrient intakes, and consequently performance. This case study reports the process of an elite male Gaelic football player (age 25 years; height, 1.88 m; body mass, 87.8 kg; lean body mass, 73.26 kg; body fat, 11.3%) transitioning from an omnivorous diet to a vegan diet at the beginning of a competitive season. The report encompasses key considerations in the planning and provision of nutrition support in this context, in addition to iterations needed based on challenges presented by the athlete. Analysis of nutrient intake (Nutritics Dietary Analysis Software), body composition (dual X-ray absorptiometry; Lunar iDXA, GE Healthcare), and running performance during match-play (global positioning system-based tracking; STATSports Apex) each indicated that with adequate knowledge and education, and appropriate planning, commitment and iterative feedback, the athlete was able to meet nutrition targets on a vegan diet without compromising key performance indicators compared to the omnivorous diet of the previous season. We anticipate that this case study will assist practitioners to recognize the key considerations to address when working with athletes transitioning to a vegan diet.